Theory development process and the fundamental explananda of strategy - Nobuiuki Costa Ito; Fernando Antônio Prado Gimenez; Paulo Hayashi Junior (Acta Scientiarum. Human and Social Sciences, 2019)
The purpose of this essay is an exploration of the current scientific status of the Strategic Management field. This essay is an attempt to open up the debate within the philosophy of strategy science, which means that the aim is to clarify critical issues related to research rather than explaining strategic phenomena. Hempel and Oppenheim’s (1948) description of explanation is the chosen framework structure as it involves the constitutive elements of a theory, as well as providing a synthesis of these elements in a single explanandum. Five main phenomena are described as the fundamental explananda, namely: (i) competitive advantage; (ii) strategic levels; (iii) the strategic process; (iv) strategy implementation; and (v) social outcomes. Relationships between these elements are assessed and commented. The paper’s purpose is not to describe a general theory of strategic management, but to induce scholars to question certain issues.